Rationale and design of the HeartFlowNXT (HeartFlow analysis of coronary blood flow using CT angiography: NeXt sTeps) study - Gaur, Sara; Achenbach, Stephan; Leipsic, Jonathon; Mauri, Laura; Bezerra, Hiram G.; Jensen, Jesper Moller; Botker, Hans Erik; Lassen, Jens Flensted; Norgaard, Bjarne Linde (Journal of Cardiovascular Computed Tomography, 2013)
Introduction: Coronary CT angiography (CTA) is an established noninvasive method for visualization of coronary artery disease. However, coronary CTA lacks physiological information; thus, it does not permit differentiation of ischemia-causing lesions. Recent advances in computational fluid dynamic techniques applied to standard coronary CTA images allow for computation of fractional flow reserve (FFR), a measure of lesion-specific ischemia. The diagnostic performance of computed FFR (FFRCT) compared with invasively measured FFR is not yet fully established. Methods/Design: HeartFlowNXT (HeartFlow analysis of coronary blood flow using coronary CT angiography: NeXt sTeps) is a prospective, international, multicenter study designed to evaluate the diagnostic performance of FFRCT for the detection and exclusion of flow-limiting obstructive coronary stenoses, as defined by invasively measured FFR as the reference standard. FFR values ≤0.80 will be considered to be ischemia causing. All subjects (N= 270; 10 investigative sites) will undergo coronary CTA (single- or dual-source CT scanners with a minimum of 64 slices) and invasive coronary angiography with FFR. Patients with insufficient quality of coronary CTA will be excluded. Blinded core laboratory interpretation will be performed for FFRCT, invasive coronary angiography, and FFR. Stenosis severity by coronary CTA will be evaluated by the investigative site in addition to a blinded core laboratory interpretation. The primary objective of the study is to determine the diagnostic performance of FFRCT compared with coronary CTA alone to noninvasively determine the presence of hemodynamically significant coronary lesions. The secondary end point comprises assessment of diagnostic accuracy, sensitivity, specificity, positive predictive value, and negative predictive value of FFRCT. © 2013 Society of Cardiovascular Computed Tomography.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Computational fluid dynamics; Computed tomography; Coronary artery disease; Coronary CT angiography; Fractional flow reserve